The Issue of Single Apartment for Foreigners in Indonesia - I Made Pria Dharsana; Desak Putu Kania Pratiwi; Rizky Mustika Rini (International Journal of Law Reconstruction, 2023)
The purpose of this study is to analyze the land rights over apartment units related to the right to ownership of apartments that can now be owned by foreign nationals. Ownership of land rights over flats does not fully adhere to the horizontal principle as stated in the UUPA. Because these rights can be owned by all ownership rights over flats. Flats can be given to anyone who qualifies as a land rights holder. The research shows that there are now many foreign nationals and foreign legal entities who own flats (apartments) in Indonesia. Both for business, investment and residential purposes. However, all actions of ownership of Sarusun, foreign citizens must still refer to the rules of law for foreign countries, as well as foreign legal entities. The ownership rules must still pay attention to the provisions of Act No. 5 of 1960 concerning Basic Regulations on Agrarian Principles (UUPA), Act No. 2 of 2011 concerning Flats, Act No. 11 of 2011 concerning Job Creation Rights, Government Regulation Number 18 of 2021 concerning Management Rights, Land Ownership Rights, Building Rights, Flat Units, and Land Registration as well as several other rules that are currently in effect.